Analysis of the Solar-Powered Street Lighting System in Petumbukan Village, Galang District, Deli Serdang - Fery Karyanta Bangun; Haris Gunawan; , Dino Erivianto (Bahasa Indonesia, 2026)
Street lighting (PJU) is a crucial infrastructure supporting social and economic activities, especially at night. Pertumbukan Village is one area that has tried implementing solar-powered street lighting as a public lighting solution. Therefore, this study was conducted to determine the street lighting system and its performance at night. This study used a descriptive-analytical approach with a case study approach and quantitative methods. The descriptive-analytical method was chosen because its primary objective was to describe the actual condition of the street lighting system. Based on the research results, the solar-powered street lighting in Petumbukan Village demonstrated quite good performance and could be operated properly. During sunny weather, all street lighting units functioned optimally with an average lighting time of 11 hours per night. The lamp's energy consumption of 660 Wh per day is much lower than the energy generated by solar panels, which is 3,600 Wh per day, so the system has a very adequate energy reserve. Although the lighting time is reduced during cloudy or rainy conditions (4–6.5 hours), the system still functions. This indicates that street lighting performance is significantly affected by weather. However, the overall system remains efficient and suitable as a solar-powered street lighting solution in rural areas. However, because system performance is significantly affected by weather, it is recommended to perform regular maintenance on the solar panels, such as cleaning the surface of the panels from dust and dirt, to maintain energy absorption efficiency. Furthermore, the energy-saving mode settings during the rainy season or during cloudy weather need to be properly adjusted to maintain optimal lighting duration.